السياق والأساليب الإنشائية الطلبية -أساليب الأمر والنهي والاستفهام أنموذجا- - عامر, سمية; حمدان, سليم (جامعة الوادي - University of Eloued, 2021)
تعد نظرية السياق (Context Theory) في الدراسات اللغوية الحديثة من أكثر النَّظريات اللغوية التصاقا بعلم الدلالة (Semantics )، وذلك لدورها الرئيس في تحديد معنى النَّصِّ وكشف مغاليقه. إننا لا نستطيع أن نقتطع الكلمة أو الجملة عمَّا سبقها أو لحقها؛ لأنَّ ذلك يؤدي إلى الغموض، فمعنى الكلمة يتحدد بالسِّياق الذي يرد فيه. ولا نعنى بالسِّياق في هذه الدراسة السِّياق اللغوي وحده دون الرجوع إلى الموقف الذي قيل فيه أو البيئة الثقافية التي نشأ فيها، وإنِّما نعني به مجموع هذه الأنواع الثلاثة. إنَّ دراسة النَّظرية السِّياقية والغوص في دقائقها ومعرفة تفاصيلها يساعدنا كثيرا فيما نريد تطبيقه، إذ بها نتمكن من تحليل الأساليب الإنشائية في اللغة العربية وفق منهج لغوي واضح، و بها أيضا نتمكن من معرفة الأسباب التي أدَّت إلى انْحِرَاف بعضها عن ظاهر معناه بشكل مفصل؛ لأنَّ الدرس اللساني القديم وإن كان قد أعطى اهتماما كبيرا للسياق ودوره في بيان الدلالة، وإن كان مقتضبا في الجانب التنظيري. The Context Theory in the modern linguistic studies is one of the linguistic theories most closely related to semantics, due to its main part in determining the meaning of the text and revealing its closures. We cannot cut or takea word or sentence from what preceded it or followed it;Because that leads to ambiguity,because the meaning of the word is determined by the context in which it is presented in. We do not mean by context in this study the linguistic context alone without reference to the situation in which it was said or the cultural environment in which it was created in, but rather we mean by it the sum of these three kinds. The study of the contextual theory and getting deep into its subtleties and knowing its details helps us a lot in what we want to apply, as with it we are able to analyze the structural methods in the Arabic language according to a clear linguistic curriculum approach, and with it we can also understand the reasons that led to the deviation of some from the apparent meaning of it in details. Because the old linguistic lesson, although it has given a greatattention to the context and its role in explaining the significance statement, and if it was albeit brief in the theoretical side.
مقال
Keywords: السياق؛ السياق اللغوي؛ سياق الموقف؛ النظرية السياقية؛ الأساليب الإنشائية; context; Linguistic context; Situation Context; Contextualtheory; Structural methods.